Representing Pancasila Values through ‘CAKRA’: The Universitas Negeri Malang Mascot in SIPEJAR-Based Educational Videos - Pratama, Yudi; Dwi Satrio, Yogi; Wibowo, Agung (Universitas Pendidikan Mandalika, 2025)
This study aims to design digital learning media in the form of 3D animated videos presenting the CAKRA mascot, which represents Malang State University (UM). This media will be uploaded on SIPEJAR as a supporting media for Pancasila Education. The research method used is Research and Development (R&D) based on the ADDIE model comprises the stages of analysis, design, development, implementation, and evaluation. It is articulated systematically at every stage by the outcome of learning needs analysis of both students and lecturers. Therefore, covered scripting and storyboarding for interactivity plus 3D animation production in Blender and Adobe Premiere Pro. The media developed was validated by subject matter experts, media experts, and language experts on a pilot test with 116 students. The results of the assessment prove that this learning media is effective at inspiration, raising motivation, and deepening students understanding as well as participation in learning about the values of Pancasila. Consequently, the use of educational mascots coming from cultural identity proves to be an innovative learning strategy for strengthening character education in digitalization.